Effect Of Ladder Drill And Saq Training (Speed, Agility, And Quikness) On Speed Running For Unimed Female Athletes Hockey Club - Siregar, Yan Indra; Arima, Putra; Rasgita, Rasgita (Jurnal Pendidikan Jasmani (JPJ), 2024)
The aim of this research was to determine the effect of Ladder Drill and SAQ (Speed, Agility and Quikness) training on running speed in UNIMED Hockey Club athletes.. The problem with this research is that there are still many athletes who are slow in their game. After observing that when athletes play games, many athletes are still slow to chase the ball, when carrying the ball and still slow to run when chasing opponents. The research method used is the experimental method and data collection techniques as well as using tests and measurements. The research design used was Pretest - Posttest Control Group Design. The number of samples in this study was 18 athletes. This research was carried out at the Unimed Multipurpose field. After carrying out the pre-test, the researcher then gave Ladder Drill and SAQ (Speed, Agility and Quikness) training in 18 meetings.. This research instrument uses a 30 m running speed test. The data analysis technique used in this research uses the t-test. From the results of statistical tests using the t-test at a significant level (α=0.05), the pre-test and post-test values ​​for the 30 meter running speed from the calculated results show that the value of tcount = 292.105 > ttable = 1.7530, so Ha is accepted and Ho is rejected. The conclusion from the results of this study is that there is a significant effect of Ladder Drill and SAQ (Speed, Agility and Quikness) training on running speed in female athletes from the UNIMED Hockey Club.